The Influence Factors Interest in Buying on E-commerce - Nuruni Ika Kusuma Wardani; Ignathia Martha Hendrati; Sishadiyati (Journal of Economics, Business, and Government Challenges, 2020)
Technology in Indonesia is currently experiencing rapid advances in informationtechnology and communication, especially internet advancements. In Indonesiaalone, people who use the Internet have increased very rapidly. With the largenumber of people using the internet in Indonesia, there is a trend of onlineshopping through websites or online shop applications. Based on these thoughts, itis interesting to examine whether the perception of ease of transaction and trustaffect buying interest in e-commerce. The population in this study are consumerswho use e-commerce. While the samples taken were 60 respondents. The analysistechnique used is Partial Least Square (PLS). From this research it can be seen thatthe perception of ease of transaction and trust can contribute to e-commercebuying interest.